MUTUAL FUND STRATEGY - Manoj Kumar Dash (International Journal of Research Science and Management, 2017)
A mutual fund is a professionally managed investment fund that pools money from many investors to purchase securities. Hedge funds are not mutual funds; they cannot be sold to the general public and are subject to different government regulations. They are generally the most common investment vehicle for retirement plans, such as the 401(k) in the United States.Mutual funds have both advantages and disadvantages compared to direct investing in individual securities.